ANALISIS EKONOMI USAHA PEMBIBITAN CABAI (Capsicum annuum L.) DENGAN TIGA JENIS BENIH DAN PERLAKUAN PEMUPUKAN - JUJUK JUHARIAH; MARGARETHA PRABA AULIA (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
The purpose of this study was to determine the most effective treatment of fertilizing doses on the results of quality tests of sprouts and growth of chilli seeds (Capsicum annuum) between bulk seeds, seeds in packaging, and direct extraction results seeds. The experimental method used was a factorial randomized block design. The first factor is the type of seeds, namely: bulk seeds (A), in packages (B), and direct extraction results (C). The second factor is the fertilizer dosage using NPK "Mutiara" (16:16:16), namely: 5 gr / l (X), 10 gr / l (Y), 15 gr / l (Z). The parameters observed included the number of live plants and the number of leaves. The results showed that the bulk seed germination power was 91.25%, the seeds were packaged and the results of direct extraction were 95.5%. After breeding and given fertilization treatment, it was found that fertilization with a dose of 5 gr / l showed the highest average growth compared to other treatments. So it can be concluded that fertilization with a dose of 5 gr / l is most effectively given to the seedling stage. Therefore fertilization with a dose of 5 gr / l is most recommended for seed producers so that the capital spent can be reduced.